Long-term variability of Jupiter's northern auroral 8-μm CH4 emissions - Sinclair, JA; West, R; Barbara, JM; Tao, C; Orton, GS; Greathouse, TK; Giles, RS; Grodent, D; Fletcher, LN; Irwin, PGJ (Elsevier, 2023)
We present a study of the long term variability of Jupiter's mid-infrared CH4 auroral emissions. 7.7–7.9 μm images of Jupiter recorded by NASA's Infrared Telescope Facility, Subaru and Gemini-South over the last three decades were collated in order to quantify the magnitude and timescales over which the northern auroral hotspot's CH4 emission varies. These emissions predominantly sound the 10- to 1-mbar pressure range and therefore highlight the temporal variability of lower-stratospheric auroral-related heating. We find that the ratio of the radiance of the poleward northern auroral emissions to a lower-latitude zonal-mean, henceforth ‘Relative Poleward Radiance’ or RPR, exhibits variability over a 37% range and over a range of apparent timescales. We searched for patterns of variability in order to test whether seasonally varying solar insolation, the 11-year solar cycle, or short-term solar wind variability at Jupiter's magnetopause could explain the observed evolution. The variability of the RPR exhibits a weak (r < 0.2) correlation with both the instantaneous and phase-lagged solar insolation received at Jupiter's high-northern latitudes. This rules out the hypothesis suggested in previous work (e.g. Sinclair et al. 2017a, 2018) that shortwave solar heating of aurorally produced haze particles is the dominant auroral-related heating mechanism in the lower stratosphere. We also find the variability exhibits negligible (r < 0.18) correlation with both the instantaneous and phase-lagged monthly-mean sunspot number, which therefore rules out a long-term variability associated with the solar cycle. On shorter timescales, we find moderate correlations of the RPR with solar wind conditions at Jupiter in the preceding days before images were recorded. For example, we find correlations of r = 0.45 and r = 0.51 of the RPR with the mean and standard deviation solar wind dynamical pressure in the preceding 7 days. The moderate correlation suggests that either: (1) only a subset of solar wind compressions lead to brighter, poleward CH4 emissions and/or (2) a subset of CH4 emission brightening events are driven by internal magnetospheric processes (e.g. Io activity) and independent of solar wind enhancements.